Síntese e caracterização das zeólitas ferrierita e ZSM-5 para pirólise de óleos vegetais - Santos, Livia Viviane dos Anjos (2014)
Pure zeolites have been studied in the processes of cracking of vegetable oils, but little is known about the potential synergistic mixtures of zeolites in the efficiency of these processes. This study examined the catalytic potential of mixtures of zeolites FER / ZSM-5 obtained by hydrothermal treatment, and compared it to the pure commercial zeolites FER and ZSM-5, and their physical mixture in catalytic pyrolysis of soybean oil. The synthesized mixtures (MSI and MSII), the physical mixture of pure commercial zeolites (MC) and individual commercial zeolites (FER and ZSM-5) were subjected to ion exchange with ammonium ion for generation of acidic materials, and characterized by XRD , IR, TG / DTG, SEM and nitrogen adsorption. The IR and XRD analyzes indi-cated the formation of the mixture FER / ZSM-5 with high crystallinity and characteris-tic peaks of zeolite materials. The thermal analysis for the synthesized mixtures had higher stages of mass loss, and their microscopies revealed typical crystals of zeolites studied. Analysis of nitrogen adsorption illustrated the microporosity of these materials. In general, the H-FER presented the best conversions of oil, followed by the H-MC physical mixture of zeolite and H-ZSM-5. The synthesized mixtures showed lower con-versions of vegetable oil.